A correlative study on the pore structure and water state of ancient decayed ivory from Sanxingdui site - Jiang, Lang; Xiang, Shilin; Wang, Yi; Jiang, Luman; Wang, Ning; Tong, Leixu; Xiao, Lin; Xiao, Qing; Wang, Fengjiao; Zhao, Lijuan; Hong, Jing (Frontiers in Earth Science, 2024)
The discovery of a large number of ancient ivory and ivory artifacts in Sanxingdui site has elevated the importance of ancient ivory relics to the level of exploring the origins of Chinese civilization. To clarify the current preservation status of decayed ivory excavated from the Sanxingdui site, we have conducted an in-depth analysis of the structure-water state relationship of the ivory unearthed from the No. 4 sacrificial pit (K4) as an example. The research indicates that the ancient decayed ivory is composed of a mixed phase of hydroxyapatite [HA, Ca10(PO4)6(OH)2] and carbonated hydroxyapatite [CHA, Ca10(PO4)3(CO3)3(OH)2], which has a mixed structure of sheet-like and needle-like crystals. The organic fibrous protein within the ivory has basically disappeared, resulting in a porous structure with a porosity of approximately 39.2%. The pore size distribution is concentrated in the range of 2.5–100 nm, dominated by mesopores, with a handful of micropores. These pore structures are occupied by adsorbed water, free water and bound water, exhibiting a high water content (35%–40%). These water molecules play a filling and supporting role in the pore structure. During the dehydration and deterioration process of the ancient decayed ivory, the loss of water support results in internal stress within the microstructure of the ivory, leading to irreversible damage such as peeling, pulverization and cracking. The correlation study between the pore structure and water state of ancient decayed ivory provides clues for tracing the geological environment, sacrificial rituals, and ecological environments of ivories in ancient times, serving as a crucial window into Earth’s history and biological evolution.